2021
DOI: 10.1007/s11325-021-02405-0
|View full text |Cite|
|
Sign up to set email alerts
|

Association between depression and sleep quality in patients with systemic lupus erythematosus: a systematic review and meta-analysis

Abstract: Background Currently, there is no consistent understanding of the relationship between depression and sleep quality in patients with systemic lupus erythematosus (SLE). This study aimed to explore the correlation between depression and sleep quality in SLE patients. Methods Five English (PubMed, Web of Science, EMBASE, Cochrane Library, and CINAHL) databases were systematically searched from inception to January 12, 2021. Two authors independently screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
1
9
0
3
Order By: Relevance
“…Because the clinical manifestations of thyroid disease are highly variable and usually nonspecific, the diagnosis of thyroid dysfunction relies primarily on laboratory biochemical tests (49). Although many studies have assessed the risk of thyroid dysfunction in patients with RA, their conclusions have been inconsistent, perhaps due to differences in the populations and geographical regions across studies (51). For example, Nazary et al compared thyroid function in 400 newly diagnosed RA patients with matched controls and found a higher prevalence of thyroid dysfunction in RA patients (25.25% vs. 11.5%; P value = 0.00001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the clinical manifestations of thyroid disease are highly variable and usually nonspecific, the diagnosis of thyroid dysfunction relies primarily on laboratory biochemical tests (49). Although many studies have assessed the risk of thyroid dysfunction in patients with RA, their conclusions have been inconsistent, perhaps due to differences in the populations and geographical regions across studies (51). For example, Nazary et al compared thyroid function in 400 newly diagnosed RA patients with matched controls and found a higher prevalence of thyroid dysfunction in RA patients (25.25% vs. 11.5%; P value = 0.00001).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms of thyroid dysfunction in patients with RA are unclear ( 51 ). Thyroid dysfunction often occurs in autoimmune thyroid disease (AITD), particularly in Hashimoto’s thyroiditis and Graves’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps then, these overlapping pathways may explain why depression and pain may act synergistically with sleep deprivation to accentuate SLE risk, as in our study. Indeed, in established SLE, these disorders are commonly reported by patients and are correlated with one another (30,31). Therefore, a better understanding of these mechanisms will not only enable us to identify effective therapeutic and prevention strategies for these disorders, but also the subsequent risk of autoimmune disease development.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that the vast majority of patients with RA have poor sleep quality, which may be associated with disease activity and ongoing inflammation (39). Likewise, patients with SLE report sleep disorders as frequent complaints with poorer sleep quality compared to the general population (40). Alterations in the immune system owing to sleep impairment may affect the course of autoimmune diseases.…”
Section: Number Of Infections In Previous 3 Months (Mean ± Sd)mentioning
confidence: 99%